2020
DOI: 10.1101/2020.10.12.20211565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Funding and COVID-19 Research Priorities - Are the research needs for Africa being met?

Abstract: Introduction Emerging data from Africa indicates remarkably low numbers of reported COVID-19 deaths despite high levels of disease transmission. However evolution of these trends as the pandemic progresses remains unknown. More certain are the devastating long-term impacts of the pandemic on health and development evident globally. Research tailored to the unique needs of African countries is crucial. UKCDR and GloPID-R have launched a tracker of funded COVID-19 projects mapped to the WHO research priorities a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…As shown in the findings, amendments were approved quickly overall. This does suggest health emergency preparedness and responsiveness 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in the findings, amendments were approved quickly overall. This does suggest health emergency preparedness and responsiveness 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on experiences from previous public health emergencies, it is clear that research review systems are central to expediency of key research questions needed to guide pandemic responses, but also that this expedience is challenged by the practical and ethical considerations that need to be made under pressure. Some of these challenges emanate from novelty of the pathogen, and thus the little data available to inform decisions about balance of risks, harms and burdens against benefits, and difficulties in determining appropriate standard-of-care, fair selection of participants, and the quality and legitimacy of informed consent [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…A review by the African Academy of Sciences (AAS) of the first seven months of Covid-19 research funding in Africa found that only 5 per cent of funded projects involved at least one African country, and only about 3 per cent of total research funding was directed to research in Africa (Antonio et al 2020).…”
Section: Unequal Access To Research Fundingmentioning
confidence: 99%
“…We have additionally now added a mapping of these same research projects against research priorities identified in the United Nations (UN) Research Roadmap for the COVID-19 Recovery 6 . We previously published a more detailed analysis on the African continent specific baseline data from this tracker in collaboration with the African Academy of Sciences 7 .…”
Section: Amendments From Versionmentioning
confidence: 99%